An Analysis of Quizizz Application in Teaching Vocabulary (JEELT : JOURNAL OF EDUCATION AND ENGLISH LANGUAGE TEACHING, 2023)
This research aims to find out how the implementation and impact of Quizizz Application in Vocabulary Teaching on class X SMAN 1 Mempawah in 2022/2023 academic year. This research will use a qualitative research method design to achieve the research objectives. This qualitative research specifically leads more to the use of the case study method. Data collection in this study was conducted using interviews (direct communication) and observation. The researcher narrates the findings based on the results of the data collection tools. In accordance with the implementation of the findings conducted by researchers, the learning stages used are three stages, namely planning, implementation, and evaluation. The use of quizizz application in vocabulary learning, helps teachers in teaching vocabulary, increases students' enthusiasm in learning vocabulary and can also build students' motivation in learning to get better grades. This research is also intended to introduce educators to quizizz applications that can be useful to help develop quality teaching and utilize technology that has been very developed in modern times.